Effect of 3 different active stretch durations on hip flexion range of motion - Ayala, F.; Sainz de Baranda, P. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to evaluate the efficacy of 3 different durations of active stretch (12 × 15, 6 × 30, and 4 × 45 seconds) in a hamstring stretching exercise program on lower extremity range of motion (ROM) in young adults. A total of 150 subjects (age, 21.3 ± 2.5 years; height, 173. 33 ± 8.35 cm; weight, 70.42 ± 10.80 kg) completed this study. Subjects were randomly assigned to 1 of 4 groups (3 treatment groups and 1 control group). The 3 treatment groups participated in an active stretching program 3 times per week for a 12-week period, holding each stretch exercise for a duration of 15, 30, or 45 seconds. The total daily dose of the stretches was 180 seconds for each group. The control group did not stretch. Passive hip flexion ROM was determined through the bilateral straight leg raise test before, during (at 4 and 8 weeks), and after the program using an inclinometer. Statistical analysis (p < 0.05) revealed a significant interaction of length of stretching program and improvement in ROM. Post hoc analysis showed that all 3 treatment groups increased hip flexion ROM from their initial values; however, the control group did not. No significant differences were found between the 3 treatment groups. This study indicates that 12 × 15-, 6 × 30-, and 4 × 45-second single durations of active stretching were equally effective at increasing hamstring length when performed 3 days per week for 12 weeks in this population.